Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Prilaku Organisasi Karyawan UMKM dSruput, Lubuk Begalung, Padang - Selvi Meiliani Saputri; Tarisya Dwi Andini; Tri Yoma Elsa; Viona Billa Ababil; Vivi Nila Sari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Contemporary drinks are rife among young people. The competition between the beverage outlets can be seen from the emergence of various unique beverage outlets. Direct observation of D'sruput MSME operations can provide an understanding of production processes, stock management, marketing strategies, and interactions with customers. Based on the results of interviews and observations obtained in the field, it was found that there were several factors of interest so that there was an interest in buying among young people, namely factors of a comfortable place, friendly service, factors of good taste where there were many variants, factors of restaurant names and unique menu names that made people interested in buying. Besides that, the price factor is quite affordable, packaging with a creative and attractive design. In addition, it was also found that personal, social and psychological factors were one of the factors in the interest in buying contemporary drinks among young people. It is hoped that this research will be useful for business people in the culinary and beverage sector as well as further research in researching business in this field.